Teachers' Linguistic Competence, Teaching Skills and Students' Linguistic Competence: Bases for a Training Design - Matalines, Ana Marie (Technium Social Sciences Journal, 2023)
This study sought to determine the correlation between teachers’ linguistic competence and students’ linguistic competence as well as between teachers’ teaching skills and students’ linguistic competence. The researcher made use of descriptive correlation to determine the relationship among the variables. Fishbowl sampling was utilized to determine public high schools for the study, and multistage sampling was used to determine the student respondents using the Raosoft sample size calculator wherein out of 1,500 students, 306 students were picked. For teacher respondents, the total population of ten (10) grade eight English teachers coming from the four select public high schools comprised the group of teacher respondents. The findings revealed that there is a significant relationship when teachers’ lesson management, assessment, and overall teaching skills were correlated with students’ linguistic competence; furthermore, in terms of teachers’ linguistic competence and students’ linguistic competence, the teachers’ grammar, textual knowledge, and overall linguistic competence show a strong correlation with students’ linguistic competence. The multiple regression analysis also revealed that teachers’ grammar, overall linguistic competence, classroom climate, and assessment predict students’ linguistic competence. With the consistency of the results on teachers’ grammar and assessment as correlates and predictors of students’ linguistic competence, a training design on grammar review based on communicative language teaching approaches with embedded authentic assessment is proposed to address the problem of students’ linguistic competence.